Uno sguardo su Pisa ellenistica da piazza del Duomo : lo scavo del saggio D 1985-1988 - Taccola, Emanuele (Access archaeology., 2019)
Excavations in Pisa carried out between 1985 and 1988 in Piazza del Duomo, close to the Leaning Tower (saggio D) provided much new data regarding the origins of the city. This book studies the ceramic finds and redefines the role of Pisa in the Hellenistic period as one of the major trade centres of northern coastal Etruria.